386 IMPACT OF REVASCULARIZATION COMPLETENESS ON ONE-YEAR OUTCOMES OF IMPELLA-SUPPORTED PCI IN ACUTE CORONARY SYNDROME: A SINGLE-CENTER EXPERIENCE. (15th December 2022) - Ruzzarin, Alessandro; Pighi, Michele; Marin, Federico; Zucchelli, Federico; Portolan, Leonardo; Mainardi, Andrea; Mora, Francesco Della; Luciano Ribichini, Flavio
Abstract: Background: The use of mechanical circulatory support in high-risk percutaneous coronary intervention (HRPCI) has grown over the past decade. We aimed to evaluate the impact of coronary revascularization extent on one-year outcomes of Impella-supported HRPCI in the setting of acute coronary syndrome (ACS). Methods: We performed a single-center retrospective study including all patients who underwent coronary angiography supported by Impella at our institution. Patients undergoing HRPCI in the setting of ACS with Impella-assistance were identified for the analysis. Revascularization extent was assessed using the British Cardiovascular Intervention Society (BCIS) jeopardy score revascularization index (RI). Patients were classified into two groups according to the completeness of revascularization in high RI (RI>0.75) and low RI (RI<0.75). The primary study endpoint was survival free from major adverse cardiac and cerebrovascular events (MACCE: all-cause death, myocardial infarction, stroke, heart failure hospitalization) at one-year follow-up. Results: Among fifty patients enrolled in the study, forty ACS patients (mean age 69.2±9 years) were identified for the analysis. At coronary angiography, 76.3% had multivessel disease, and the mean BCIS-JSPRE-PCI score was 10.2±2.1. After Impella-supported PCI, BCIS-JSPOST-PCI score was 2.1±2.0 (p<0.01) and RI>0.75 was reached in 89.2% of cases (mean RI 0.8±0.2). In-hospital mortality was 20.5% without a statistical difference between high and low RI (p=0.1). Within 12 months, time-to-MACCE was statistically higher in patients with high RI as compared to low RI (288.2 vs. 189.8 days, p<0.05) (Figure). Conclusions: Our single-center experience suggests a more extensive revascularization, aiming for a positive impact on outcomes, when a Impella-protected strategy is performed in the setting of acute coronary syndromes.